Remote Origins: 'Water Towns', Olbicella, and the root *alb- (Origini remote. Il caso delle “città d’acqua”, di Olbicella e della radice *alb-) - Perono Cacciafoco, Francesco (2016)
This paper outlines a new applied epistemological aspect of the New Convergence Theory (NCT), aimed at developing a potentially 'homogeneous' vision among the different approaches in the field of Indo-European Linguistics. This work tries to reconstruct an Italian and European 'macro-area' (or 'micro-area') characterized by places names linked to the root *alb-, with a delineation of the 'semantic steps' produced, over time, by the same root, following a potentially 'all-embracing' approach. It seems that Paleo-Ligurian place names of the type Alba, old European river names Albis and the like, as well as their ablauting forms Olb- (> Orb- in Romance Ligurian), do not reflect directly the proto-Indo-European adjective *albho-, 'white'; rather, they all seem to continue a pre-proto-Indo-European extended root *Hal-bh-, 'water', cognate with the Sumerian ḫalbia (> Akkadian ḫalpium, 'spring', 'well', 'water mass', 'water hole'). A further analysis of the same *Hal-bh-, moreover, leads to a comparison with the proto-Indo-European root *Hal-, 'nourish'. The proto-Indo-European suffixed form *HwaH-r-, 'water', then, seems to exhibit a similar diffusion. As told above, this work is aimed at the 'reconstruction' of a toponymic 'macro-area' (or 'micro-area', depending on the points of view) related to the root *alb- and to the 'semantic steps' linked to the same root, with regard, especially, to the Northern Italy (and, secondarily, to Europe), developing – remaining in the specific case of pre-Latin (pre-Indo-European, proto-Indo-European, and Indo-European) Toponymy – this onomastic aspect of the New Convergence Theory (NCT) in relationship to the different approaches of the Indo-European Linguistics (the Indo-European / Glottological, the pre-Indo-European, the pan-Indo-European, the pan-Semitic, the Paleolithic Continuity Paradigm / Paleolithic Continuity Theory / Teoria della Continuità, the Vasconic Substratum Theory, the Glottalic Theory, for example). The New Convergence Theory (NCT), indeed, is mainly aimed at developing a potentially 'homogeneous' vision among the different above mentioned approaches in the field of Indo-European Linguistics, without emphasizing any one in particular, but trying to outline an 'all-embracing' reconstruction that takes into account each of the scientific achievements of the other considered Theories. This paper, therefore, is a theoretical work with applied implications both in the ambit of Toponymy / Toponomastics, and in the field of Semantics, with a specific focus on the delineation of an 'ideal map' related to the notion of 'water' and on the identification of 'water places' in the analyzed area.